Perchlorate Exposure is Associated with Oxidative Stress and Indicators of Serum Iron Homeostasis among NHANES 2005–2008 Subjects. Issue 10 (January 2015) - Schreinemachers, Dina M.; Ghio, Andrew J.; Sobus, Jon R.; Williams, Marc A.
Perchlorate (ClO4 – ), an oxidizing agent, is a ubiquitous environmental pollutant. Several studies have investigated its thyroid hormone disrupting properties. Its associations with other biological measures are largely unknown. This study, combining 2005–2008 National Health and Nutrition Examination Surveys, investigated associations between urinary perchlorate and biomarkers of iron homeostasis, lipids, blood cell counts, and glucose metabolism. Healthy males (n = 3705), non-pregnant females (n = 2967), and pregnant females (n = 356), aged 12–59 years, were included in the linear regression models, which showed significant positive (+) and negative (−) associations for both males and non-pregnant females with serum uric acid (−), serum iron (−), RBC count (−), blood urea nitrogen (+), and lymphocyte count (+). Other significant associations were observed for either males or non-pregnant females. Among pregnant females, perchlorate was significantly associated with blood urea nitrogen (+) and serum iron (−). These associations may be indicators of perchlorate's potential effect on several biological systems, which when considered in total, may implicate perturbation of iron homeostasis.